Relationship between saturation and contrast during internal limiting membrane peeling in 3D digital vitreoretinal surgery: A retrospective study - Saaya Fukase; Yoshihito Sakanishi; Keiji Matsumoto; Ayumi Usui-Ouchi; Shintaro Nakao; Nobuyuki Ebihara (PLoS ONE, 2025)
This retrospective comparative study aimed to investigate the relationship between saturation and contrast when using Brilliant Blue G (BBG) staining in internal limiting membrane (ILM) peeling during vitreoretinal surgery using the NGENUITY® 3D Visual System (NGENUITY), a three-dimensional digital monitor. Participants were individuals undergoing vitreoretinal surgeries involving ILM peeling with BBG staining, performed by the same surgeon at Juntendo University Urayasu Hospital, from October 2022 to June 2023, using the NGENUITY system. After ILM peeling, the contrast ratio between the ILM-peeled area and stained area was calculated using normal color tone (Normal group) and color tone set to yellow, with saturation set to 0 (Monochrome-0 group) or 20 (Monochrome-20 group). The visibility of retinal hemorrhage was also examined. The findings were compared among the groups. The contrast ratios of surgical screens with different color settings were used as the main outcome measure. We included 27 patients (27 eyes; 16 female individuals; age: 68.9 ± 9.8 years). The contrast ratios were 1.62 ± 0.15, 2.05 ± 0.44, and 2.00 ± 0.51 in the Normal, Monochrome-0, and Monochrome-20 groups, respectively. The contrast ratios were significantly higher in the Monochrome-0 and Monochrome-20 groups than in the Normal group (both p < 0.01), whereas these ratios were similar in the Monochrome-0 and Monochrome-20 groups (p = 0.554). Although distinguishing retinal hemorrhage was difficult in the Monochrome-0 group, this distinction was possible in the Monochrome-20 group. In BBG staining of the ILM, using the monochromatic mode with the NGENUITY system improves contrast visibility; however, using slight saturation facilitates distinction of retinal hemorrhage and allows safe ILM peeling.